LIFE HISTORY, BEHAVIOR AND MORPHOLOGY OF THE IMMATURE STAGES OF ENOCHRUS QUADRIPUNCTATUS HERBST IN THE LABORATORY (COLEOPTERA: HYDROPHILIDAE) I- LIFE HISTORY AND BEHAVIOR (Journal of Sciences, Islamic Republic of Iran)
The life history of Enochrus quadripunctatus Herbst was studied in the laboratory. The duration of each developmental stage, larval behavior, and preimaginal mortality rate were determined. It takes the insect a total of 43 days from hatching to reach the adult stage, with a high mortality rate in the first stadium. The mortality rate decreases as the beetle passes through the immature stages. Although the species is basically similar to the other hydrophilids studied thus far, some differences with those reared in the laboratory, such as time of each developmental stage, larval behavior, and mortality rate have been observed.